2017
DOI: 10.3389/fmicb.2017.00465
|View full text |Cite
|
Sign up to set email alerts
|

M. tuberculosis Hypothetical Proteins and Proteins of Unknown Function: Hope for Exploring Novel Resistance Mechanisms as well as Future Target of Drug Resistance

Abstract: Drug resistance in tuberculosis predominantly, mono-resistance, multi drug resistance, extensively drug resistance and totally drug resistance have emerged as a major problem in the chemotherapy of tuberculosis. Failures of first and second line anti-tuberculosis drugs treatment leads to emergence of resistant Mycobacterium tuberculosis. Few genes are reported as the principal targets of the resistance and apart from the primary targets many explanations have been proposed for drug resistance but still some re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 21 publications
0
15
0
1
Order By: Relevance
“…There were still some EMB-resistant isolates determined by phenotypic DST methods (PM, MGIT, and MABA), which lacked embAB mutations. This implied that these strains probably harbored mutations outside embAB (Safi et al, 2013;He et al, 2015;Tulyaprawat et al, 2019) or that the resistance may have been caused by other mechanisms, such as overexpressed efflux pumps and loss of porins (Sharma and Bisht, 2017;Sharma et al, 2018). Careful interpretation of a negative DNA sequencing result (no mutation) is thus necessary in the accurate management of suspected DR-TB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were still some EMB-resistant isolates determined by phenotypic DST methods (PM, MGIT, and MABA), which lacked embAB mutations. This implied that these strains probably harbored mutations outside embAB (Safi et al, 2013;He et al, 2015;Tulyaprawat et al, 2019) or that the resistance may have been caused by other mechanisms, such as overexpressed efflux pumps and loss of porins (Sharma and Bisht, 2017;Sharma et al, 2018). Careful interpretation of a negative DNA sequencing result (no mutation) is thus necessary in the accurate management of suspected DR-TB.…”
Section: Discussionmentioning
confidence: 99%
“…However, the presence of these mutations in embAB was also observed in EMBsusceptible isolates (Shi et al, 2011;Zhao et al, 2015;Li et al, 2016;Sun et al, 2018). Besides, there are no mutations within the particular genes responsible for EMB resistance in some EMB-resistant isolates, implying the involvement of other resistance mechanisms (Sharma and Bisht, 2017;Sharma et al, 2018). As per the literature, significant discordance exists between the phenotypic and genotypic methods for EMB susceptibility testing (Kim, 2005;Garrigo et al, 2007;Cheng et al, 2014;Zhang et al, 2014).…”
Section: Introductionmentioning
confidence: 91%
“…Expression proteomics {2-dimensional gel electrophoresis (2-DE)} coupled with MALDI-TOF-MS and bioinformatic tools has emerged as a direct approach for the separation, identification and characterization of proteins which could be used to find out potential drug targets and diagnosis of resistance as well as pathogenesis [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. Since the last decade, a panel of discovery (expression), targeted proteomics and bioinformatics-based studies [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ] have been accumulated on M. tuberculosis pathogenesis and drug resistance which showed differential expression of a panel of known and unknown proteins and suggested that these proteins might be used in diagnostics and as drug targets against drug resistant TB. We have previously reported that Rv0148 (hypothetical protein/putative short-chain type dehydrogenase/reductase) was overexpressed in aminoglycosides-resistant M. tuberculosis .…”
Section: Proteomics and Bioinformatics Explored Potential Drug Tarmentioning
confidence: 99%
“…Differential expressions of known and hypothetical proteins (functionally unknown) have reported in drug-resistant strains of M. tuberculosis. In-silico analysis (Molecular Docking, KEGG Pathways, Pupylome, and Interactome) of these proteomes explored the possible pathways as well as subsequent targets involved in the drug resistance [16][17][18][19][20][21]. Selected proteins and subsequent targets of the affiliated pathways might serve as the possible diagnostics and therapeutic targets for the development of alternative strategies against the drug resistance.…”
Section: Proteomics and Bioinformatics: Possible Diagnostics And Thermentioning
confidence: 99%